Modal and flutter analysis of the sailplane LAK-17B using numerical methods - Andrikaitis, Marius; Fedaravičius, Algimantas (Transport, 2014)
The objective of current work is to determine the V–g and V–f diagrams for the sailplane’s LAK-17B empennage using numerical methods. The article considers the following problems: development of finite element model of the sailplane LAK-17B; normal modes calculation using created finite element model; flutter analysis of sailplane LAK-17B using doublet lattice method. First Published Online: 25 Mar 2014